Kesadaran dan Tanggung Jawab Guru Terhadap Pelaksanaan Peran dan Fungsi Guru Dalam Mendidik dan Mengajar di SMP Negeri 24 Medan - Putri Widia; Nazlah Aulia; Marly Meani; Kania Nova; Talita Sembiring; Gadis Prasiska; Jamaludin Rumi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The role of a teacher is very important to the formation of students at school. So it takes full awareness by a teacher regarding his role and function as a professional teacher. Thus the title of this study is the awareness and responsibility of teachers towards the implementation of the roles and functions of teachers in educating and teaching. The purpose of this research is to find out how the awareness and responsibility of teachers towards the implementation of the roles and functions of teachers in educating and teaching at SMPN 24 Medan. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and interview questionnaires given to students. The results of this study indicate that teachers' awareness and responsibility are very important in implementing their roles and functions as educators and teachers. It takes good cooperation between teachers and principals along with other supporters such as adequate facilities.